2010
DOI: 10.2174/1875043501003010010
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Acyclovir Through Bioengineered Corneal Implants with Silica Nanoparticle Carriers~!2009-08-29~!2010-01-05~!2010-03-18~!

Abstract: Abstract:Herpes simplex virus (HSV) infection is the most common cause of corneal blindness in the Western world. Despite effective anti-viral drugs such as acyclovir (ACV), disease recurrence due to the virus establishing latency within the corneal nerves and possibly cells makes treatment very challenging. Furthermore, although effective, current systemic and topical preparations of anti-viral drugs do not appear to deliver sufficient quantities to the cornea to prevent reactivation. Current treatment for HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…shown that it is possible to deliver drugs such as antibiotics (Riau et al, 2015), anti-virals (Bareiss et al, 2010) peptides with anti-viral activity or even transfected cells that produce peptides with antiviral activity .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…shown that it is possible to deliver drugs such as antibiotics (Riau et al, 2015), anti-virals (Bareiss et al, 2010) peptides with anti-viral activity or even transfected cells that produce peptides with antiviral activity .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…25 Briefly, 4 mL cyclohexane (Acros Organics, Morris Plains, NJ) was combined with 1 mL Triton (Sigma-Aldrich), followed by the addition of a 1 mL LL-37 solution (14 mg/mL). Under magnetic stirring, 0.75 mL tetraethyl orthosilicate (TEOS; Sigma-Aldrich) was added dropwise, followed by slow neutralization of the mixture using concentrated ammonia hydroxide (target pH was 4.0-6.0).…”
Section: Composite Collagen-mpc Hydrogels Containing Sinp Encapsulatementioning
confidence: 99%
“…GNPs and GNPs@Bevacizumab were incubated with different concentrations of NaCl solutions (4,8,16,25 and 50 mM) in a 1:1 volume ratio. All the samples were incubated at room temperature for 10 minutes and the hydrodynamic diameter, zeta potential and UV-visible absorbance were measured.…”
Section: Flocculation Testmentioning
confidence: 99%